Reconstructing Miocene bird mating behavior from a fossil tracksite - Nasrollah Abbassi (Scientific Reports)
Abstract Ichnofossils are important in paleoecological studies, interpreted as fossilized behaviors. Vertebrate footprints, a type of ichnofossils, can reveal the movements of trackmakers. By examining fossil footprints in groups and comparing them to modern counterparts, we can gain insights into other animal behaviors, such as social interactions. Here, a Miocene bird mating site is introduced, that is the first report of fossil of bird mating dance behavior. This trace fossil was found in the Miocene Upper Red Formation in northwest Iran. The slab contains seven inferred behaviors left behind during male mating dances, including walking, high stepping, stomping in place, short-distance flying, hopping, pecking, and lateral leaping. Statistical analysis reveals that walking and high stepping are the most abundant, with most often lateral leaping transitioning to high stepping. Stomping in place and hopping typically occur during walking, while short-distance flying is associated with high stepping. Comparing the footprints by size and body mass (estimated hip height ~ 60 mm, weight ~ 320 gr) and interpreting behaviors with modern ones suggests that members of Charadriidae, likely plovers, were the trackmakers. Based on this fossil behavior, a new ethological class of trace fossils, Goshnichnia is introduced for all trace fossils showing mating behavior.